2022
DOI: 10.1177/19476035221144746
|View full text |Cite
|
Sign up to set email alerts
|

Toward New Assessment of Knee Cartilage Degeneration

Abstract: Objective Assessment of human joint cartilage is a crucial tool to detect and diagnose pathological conditions. This exploratory study developed a workflow for 3D modeling of cartilage and bone based on multimodal imaging. New evaluation metrics were created and, a unique set of data was gathered from healthy controls and patients with clinically evaluated degeneration or trauma. Design We present a novel methodology to evaluate knee bone and cartilage based on features extracted from magnetic resonance imagin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 54 publications
0
1
0
Order By: Relevance
“…In addition, a high degree of heterogeneity was appreciated based on mean follow‐up times, grading systems for cartilage damage, definition of failure, reporting of both cartilage defect size and concomitant cartilage procedures, further limiting the authors' ability to perform any meaningful statistical analyses evaluating the predictive capacity of these variables on outcomes. Indications for MAT were consistent among studies, while the reliability of cartilage status grading has been shown to have questionable reliability [3]. Furthermore, there is a relative scarcity of literature on the topic of MAT in patients with increasing degrees of cartilage damage, which could be explained by the fact that increasing grades of osteoarthritis have been a traditional relative contraindication for MAT procedures.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a high degree of heterogeneity was appreciated based on mean follow‐up times, grading systems for cartilage damage, definition of failure, reporting of both cartilage defect size and concomitant cartilage procedures, further limiting the authors' ability to perform any meaningful statistical analyses evaluating the predictive capacity of these variables on outcomes. Indications for MAT were consistent among studies, while the reliability of cartilage status grading has been shown to have questionable reliability [3]. Furthermore, there is a relative scarcity of literature on the topic of MAT in patients with increasing degrees of cartilage damage, which could be explained by the fact that increasing grades of osteoarthritis have been a traditional relative contraindication for MAT procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Patients diagnosed with Degenerative OA (D) and healthy Control subjects (C) were recruited within the EU project RESTORE (https://restore-project.ru.is, accessed 1 July 2022). A further explanation of the acquisition protocol and the facilities utilized is described in a previous work [19].…”
Section: Clinical Datamentioning
confidence: 99%